Digital Content Implementation as a Transformation of Digital Marketing Strategy for Computer Service MSMEs: A Community Service Program for Alify MSME in Pananjung Village, Pangandaran, West Java - Astri Wulandari; Riska Aprilina (Golden Ratio of Mapping Idea and Literature Format, 2026)
Digital technology has transformed MSME marketing, yet many Indonesian micro-enterprises still rely on conventional promotion. This Community Service Program implemented digital content creation to strengthen Alify MSME’s marketing strategy in Pananjung Village, Pangandaran, using an Appropriate Technology approach integrated with Participatory Action Research. Activities included a pre-survey of 30 customers, needs assessment, content design, practical training, mentoring, and post-evaluation. The validated instrument measured digital brand awareness, content quality, promotional affordability, and customer interaction satisfaction. The average score increased from 1.87 to 4.12, with a 120.3% improvement, an N-Gain of 0.75, and significant paired t-test results across all dimensions. Alify also independently managed two social media accounts, gained 127 followers, achieved 4.8% engagement, and produced a practical digital marketing guide sustainably.